Crimes and punishment: understanding of the criminal code - Jung, Sandy; Ahn-Redding, Heather; Allison, Meredith (My University, 2014)
Knowledge about criminal laws is expected in our society. There are many important reasons why accurate knowledge should be expected, such as the deterrence of citizens from engaging in illegal conduct and the assurance that people are making sound decisions about supporting or not supporting changes in the criminal justice system. This study surveyed 301 undergraduate students about their knowledge of criminal laws and their associated sentences. Our results indicate that participants were accurate in defining theft and the ages for legal use of substances and identifying whether specific scenarios are considered sexual offences, but less able to define the blood alcohol level for impaired driving, dangerous driving, sexual interference, and aggravated sexual assault. With regards to sentencing dispositions, participants were not consistently accurate. They also tended to inflate the likelihood of reoffending in general, particularly violent and sexual offending. Prior exposure to the criminal justice system did not seem to be associated with crime and sentencing knowledge or recidivism estimations. Our findings identify areas where young adults are unaware of legal definitions of crimes and their punishments and solicit the need to find innovative ways to educate young adults on the Criminal Code.
Keywords: criminal code; sentencing; knowledge; young adults